Carbon Electrode-Based Sensors for Detecting Endocrine-Disrupting Chemicals: A Literature Review and Development Prospects - Zulkarnain , Muh Aryo (Science Tech Group, 2024)
Stunting remains a serious global health issue, with its impact particularly felt in developing countries. The problems arising from this issue are not only related to nutritional intake but also to exposure to toxic substances known as Endocrine-Disrupting Chemicals (EDCs), such as pesticides, which have become one of the key indicators of the primary causes. Pesticide exposure can disrupt thyroid hormone function in the body, as this hormone plays a crucial role in the growth and development of children. This article presents a literature review on detection technologies for pesticides categorized as Endocrine-Disrupting Chemicals (EDCs) and recent efforts in developing voltammetry-based electrodes for the early detection of stunting. Exposure to EDCs, such as fipronil and bisphenol-A, has been linked to stunting, reinforcing the urgency for early detection. Electrochemical methods, particularly voltammetry, show promise for detecting EDCs with high sensitivity. Recent research highlights the use of carbon electrodes, including those derived from agricultural waste like palm oil shells, as cost-effective and environmentally friendly alternatives for working electrodes. Although still in the development stage, carbon electrodes offer a promising solution for early stunting detection through EDC detection. This study underscores the importance of developing rapid, accurate, and economical detection technologies to address global health challenges.